Fat tissue as an embolic material changes the embolization time in a size-dependent manner: a basic investigation using rabbits - Takaki, Kai; Nitta, Norihisa; Ota, Shinichi; Inoue, Akitoshi; Watanabe, Yoshiyuki (Japanese journal of radiology, 2021)
Purpose To evaluate the usefulness of fat tissue as an embolic material and determine whether the embolization time depends on the size of the fat tissue. Materials and methods Inguinal fat tissues from 16 rabbits were processed as follows: (1) fat tissues were cut into 2-mm squares, and (2) fat tissue squares were dissociated 20 × through a syringe without a needle (1–139 μm in diameter). The distal main trunk of the right or left renal artery was completely embolized using one of the two types of fat tissue. After 1 or 7 days, renal angiography was performed. Results On day 1 after embolization of the renal artery with 2-mm fat tissue squares (Group 1–1) and on day 7 (Group 1–2), the reperfusion rates were 4.0 ± 5.5% and 29.9 ± 6.9%, respectively. On day 1 after embolization of the renal artery with fat tissues dissociated using a 20 × pumping cycle (Group 2–1) and on day 7 (Group 2–2), the reperfusion rates were 59.9 ± 9.9% and 74.3 ± 26.0%, respectively. The reperfusion rates were significantly different between the two types of fat tissue. Conclusions Fat tissue serves as an embolic material that changes the embolization time in a size-dependent manner.